Utilizing of Project-Based Learning to Increase Students’ Vocabulary Mastery at the Tenth Grade of Senior High School - Sudirman, Andi Mangngunrungi; Iluh Meriyani (Institut Agama Islam Negeri Palopo, 2025)
This study aims to determine the increasing of students’ vocabulary mastery at the tenth grade of SMAN 9 Luwu Utara through the utilized of Project-Based Learning. The researcher used quantitative method with pre-experimental design. This research employed vocabulary test as the research instrument in the form of multiple choice. This research was held at SMAN 9 Luwu Utara. The population of this research consisted of tenth grade students of SMAN 9 Luwu Utara. The total of the population were 100 students, while the sample consisted of 25 students. This research implemented a total purposive sampling technique to determine the sample. In collecting the data, the pre-test, treatment and post-test were used. However, the data were analyzed by using paired sample t-test. The researcher found that there was a significant difference between students’ mean scores in the pre-test and post-test. The students’ mean score in the pre-test was 55.68 while, students’ mean score in the post-test was 82.44. besides that, based on the result of paired sample t-test shown that sig (2-tailed) ˂ α (0.000 ˂ 0.05) means that there is a significant difference between learning outcomes in pre-test and post-test data. Hence, H0 is rejected and H1 is accepted. It can be concluded that the concept of project-based learning applied through video vlog design at tenth grade had an effective impact on increasing students’ vocabulary master and also utilising project-based learning in the form of making videos can build collaboration and raise communication between students with the groups formed.